Nursing Practice for Older Adults with Comorbid Dementia and Cancer by Certified Nurse Specialists in Gerontological Nursing: A Qualitative Study - Senuma, Maiko; Kyota, Ayumi; Tsukagoshi, Noriko; Ushikubo, Mitsuko; Kondo, Yuka (Journal of Japanese Society of Cancer Nursing, 2025)
Objective: The study aimed to identify effective nursing practices of certified nurse specialists in gerontological nursing (GCNS) for older adults with dementia and cancer.Methods: Semi-structured interviews were conducted with seven GCNSs, and the data were qualitatively analyzed.Results: The narratives of the subjects were nursing practice in acute care hospitals, special nursing homes and/or home care nursing. As nursing practice for older adults with both dementia and cancer, 66 codes, 11 subcategories and 3 categories were identified: alleviating complicated physical and psychological pain caused by cancer and dementia, harnessing the positive aspects of cancer and dementia coexistence and examining the meaning of cancer diagnosis and treatment for people with dementia.Conclusions: The GCNSs alleviated the complicated physical and psychological pain caused by cancer while taking the patient's dementia into consideration. They provided nursing care that makes the coexistence of dementia and cancer advantageous for patients, such as greater access to medical and welfare services and more predictability of disease status. Because dementia makes it difficult for nurses to understand patients’ intentions, the meaning of cancer diagnosis and treatment for patients was discussed together with their families and support providers.